Preparation method of cobalt-doped mesoporous HAP catalyst and application of cobalt-doped mesoporous HAP catalyst in toluene oxidation reaction

Preparation of cobalt-doped mesoporous HAP catalyst by sol-gel method solves the problems of poor low-temperature activity and poor thermal stability in toluene catalytic oxidation reaction in the prior art, and achieves efficient catalytic oxidation effect of toluene and reduces the synthesis cost.

CN119259103APending Publication Date: 2025-01-07SHENYANG NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411644590.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The supported catalysts prepared by the existing impregnation method have problems such as poor low-temperature catalytic activity and poor thermal stability in toluene catalytic oxidation reaction.

Method used

The cobalt-doped mesoporous HAP catalyst was prepared by sol-gel method, nano HAP was prepared by adjusting pH value, solution concentration and aging time, combined with freeze-drying method, and immersing the Co and Pt precursors on the surface of the HAP support using the immersion method, and Heat treatment was performed to obtain a uniformly dispersed supported Pt/Co-HAP or Pt-Co/HAP catalyst.

Benefits of technology

The catalytic oxidation performance of low-temperature toluene is improved, and the complete conversion of toluene at a lower temperature is achieved. The preparation process is simple, the cost is low, the catalyst is dispersible and the activity is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259103A_ABST
    Figure CN119259103A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a cobalt-doped mesoporous HAP catalyst and application of the cobalt-doped mesoporous HAP catalyst in toluene oxidation reaction, and belongs to the technical field of catalyst preparation. The catalyst is prepared by adopting a sol-gel-dipping-heat treatment three-step method, firstly, nano HAP with different morphologies and pore structures is prepared by adjusting the process conditions of pH, solution concentration, aging time and the like in combination with a freeze-drying method, then Co and Pt precursors are dipped on the inner surface of an HAP carrier by adopting an equivalent-volume dipping method, and the catalyst is prepared. And finally, carrying out heat treatment on the catalyst to obtain a uniformly dispersed supported Pt-Co / HAP catalyst, preparing cobalt modified HAP, and dipping platinum by using the cobalt modified HAP as a carrier to obtain the Pt / Co-HAP catalyst. Co doping enhances the interaction between the metal and the carrier, so that Pt particles are highly dispersed, the performance of low-temperature toluene catalytic oxidation is improved, the preparation method is simple, quantitative loading of Co and Pt can be realized, and the catalytic performance of toluene oxidation is improved through the synergistic effect of the metal Pt, Co and the HAP carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, and in particular to a preparation method of a cobalt-doped mesoporous HAP catalyst and application of the catalyst in a toluene oxidation reaction. Background Art

[0002] Hydroxyapatite (HAP) has good biocompatibility, bioactivity, thermal stability, ion exchange, adsorption and other advantages and is widely used in biomedical materials, environmental functional materials, humidity-sensitive semiconductor materials, catalyst carriers and other aspects. The preparation methods of hydroxyapatite are divided into dry method and wet method. The dry method is a solid-state reaction method, which means that solid calcium salt and phosphate are fully mixed under certain conditions to generate hydroxyapatite; the wet method is divided into sol-gel method, hydrothermal synthesis method, chemical precipitation method and microemulsion method. The sol-gel method has attracted much attention because it does not require vacuum and high temperature. The sol-gel method has a high product purity, the material preparation process is easy to control, and the molecular-level mixing during the reaction process improves the dispersion and uniformity of the reaction system, which is conducive to the formation of uniform and fine nano-scale HAP. Compared with the traditional process, the temperature of the sol-gel process is low, generally room temperature or slightly higher temperature, the prepared material particles are small and uniform, and the proportion of each component is easy to control, and the introduction of impurities can be reduced, which can ensure the purity of the final product.

[0003] In recent years, the emission of volatile organic compounds (VOCs) has been increasing, seriously endangering the environmental air quality and human health. At present, a large number of technologies have been applied to the removal of VOCs. Among the many technologies for removing VOCs, catalytic oxidation technology is considered to be one of the technical means with potential application value. At present, a large number of catalysts have been applied to the catalytic oxidation of VOCs, such as rare earth oxides, transition metal oxides, and precious metal catalysts. Among the many transition metal oxides, cobalt-based catalysts have the advantages of low price, environmental friendliness, and good thermal stability, so they are widely used in the field of heterogeneous catalytic oxidation.

[0004] Patent CN107190300B discloses a method for preparing a mesoporous hydroxyapatite nanoparticle / titanium dioxide nanotube array composite material, in which hydroxyapatite is prepared by a sol-gel method. Hexadecyltrimethylammonium bromide is used as a template, (NH4)2HPO4 is used as a phosphorus source, Ca(NO3)2·4H2O is used as a calcium source, the pH value is adjusted to 10 with ammonia water, stirred for 2-4 hours, aged for 24-48 hours, centrifuged and washed alternately with ethanol and distilled water, freeze-dried at -50 °C for 48 hours, and then calcined at 500-600 °C for 4-6 hours to obtain mesoporous hydroxyapatite nanoparticles. HAP particles are modified on the surface of the titanium dioxide nanotube array to load some drug molecules as a carrier for sustained drug release.

[0005] However, among the above prior arts, the preparation of supported catalysts by the impregnation method has technical problems such as poor low-temperature catalytic activity and poor thermal stability in the catalytic oxidation reaction of toluene. Summary of the invention

[0006] The technical problem to be solved by the present invention is to address the deficiencies of the above-mentioned prior art and to propose a preparation method of a cobalt-doped mesoporous HAP catalyst and its application in toluene oxidation reaction.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical scheme is adopted: A method for preparing a cobalt-doped mesoporous HAP catalyst comprises the following steps: 1). Preparation of precursor HAP colloid: The solutions of the calcium source and the phosphorus source are mixed, magnetically stirred, and the pH value of the solution is adjusted; 2). Preparation of ultra-light mesoporous nano-HAP: The precursor was aged and then freeze-dried to obtain ultralight mesoporous nano-HAP; 3). The ultralight mesoporous nano-HAP prepared in step 2) is used as a carrier to prepare a supported Co catalyst or a supported Pt-Co catalyst or a supported Pt / Co catalyst by an impregnation method; 4). Heat-treating any one of the supported catalysts obtained in step 3) to obtain a Co / HAP catalyst or a Pt / Co-HAP catalyst or a Pt-Co / HAP catalyst.

[0008] The specific steps of obtaining the Pt / HAP catalyst are as follows: placing the ultralight mesoporous nano-HAP as a carrier in a beaker, immersing it in a 1 wt% chloroplatinic acid solution under stirring, drying it at 50 °C to obtain a supported nano-Pt catalyst, and performing heat treatment.

[0009] The specific steps of obtaining the Co / HAP catalyst are as follows: placing the ultralight mesoporous nano-HAP as a carrier in a beaker and immersing it in a 15 wt.% cobalt nitrate solution, and then drying and heat treating it at a temperature of 30-90°C.

[0010] The specific steps of obtaining the Pt-Co / HAP catalyst are as follows: placing the ultralight mesoporous nano-HAP as a carrier in a beaker, impregnating it with 1 wt.% chloroplatinic acid and 15 wt.% cobalt nitrate solution in one step, drying it at a temperature of 30-90°C, and then heat treating the dried sample.

[0011] The specific steps of obtaining the Pt / Co-HAP catalyst are as follows: placing the ultralight mesoporous nano-HAP as a carrier in a beaker, impregnating it with a 15 wt.% cobalt nitrate solution under stirring, drying it at a temperature of 30-90°C, heat-treating it, and then impregnating it with a 1 wt.% chloroplatinic acid solution, and drying it in a 50°C oven; and then heat-treating the dried catalyst sample.

[0012] Preferably, the step 1) adopts a sol-gel preparation method, specifically: Dissolve the soluble calcium salt in deionized water, slowly drip the phosphorus source into the calcium salt solution, then drip into the citric acid solution, stir for 0.1-5 h at a temperature of 30-90 °C; then add ammonia water to the solution, adjust the pH value to 8-12, continue stirring for 0.5-6 h, and age for 6-72 h to obtain HAP gel.

[0013] Preferably, in step 2), the HAP gel is freeze-dried for 12-48 h to obtain an ultralight mesoporous HAP material.

[0014] Preferably, the molar ratio of calcium ions in the soluble calcium salt to phosphorus ions in the phosphorus source is 5:3.

[0015] Preferably, the soluble calcium salt is one of calcium nitrate, calcium chloride or calcium hydroxide; and the phosphorus source is one of phosphoric acid, diammonium hydrogen phosphate, disodium hydrogen phosphate or dipotassium hydrogen phosphate.

[0016] Preferably, citric acid is used as the chelating agent, and the molar ratio of citric acid to soluble calcium salt is 2:1.

[0017] As another technical solution of the present invention, a cobalt-modified HAP carrier is prepared by a sol-gel method, specifically, soluble calcium salt and cobalt salt are dissolved in deionized water, a phosphorus source is slowly dripped into the mixed solution of calcium salt and cobalt salt, and stirred for 0.1-5 h at a temperature of 30-90 ° C. Secondly, ammonia water is added to the solution to adjust the pH value to 8-12, stirring is continued for 0.5-6 h, and aging is performed for 6-72 h to obtain a HAP gel. Finally, the HAP gel is freeze-dried to obtain a cobalt-modified HAP carrier with a cobalt content of 0.01-20 wt%.

[0018] As another technical solution of the present invention, the cobalt-doped mesoporous HAP catalyst prepared according to the above preparation method is used in toluene oxidation reaction.

[0019] Compared with the prior art, the present invention achieves the following technical effects: The present invention provides a method for preparing a cobalt-doped catalyst for toluene oxidation reaction, which adopts a sol-gel-impregnation-heat treatment three-step method to prepare the catalyst. First, by adjusting the process conditions such as pH value, solution concentration, aging time, etc., a nano-HAP with different pore structures is prepared in combination with a freeze-drying method, and then Co and Pt precursors are impregnated into the surface of the HAP carrier by an equal volume impregnation method. Finally, the catalyst is heat-treated to obtain a uniformly dispersed supported Pt / Co-HAP or Pt-Co / HAP catalyst. Co doping enhances the interaction between the metal and the carrier, so that the Pt particles are highly dispersed, and the performance of low-temperature toluene catalytic oxidation is improved. Toluene can be completely converted at a relatively low temperature. The present invention has a simple preparation method, can achieve quantitative loading of Co and Pt, and the prepared nano-cobalt-doped mesoporous HAP catalyst has Pt nanoparticles in a uniformly dispersed state. The synergistic effect between the metal Pt, Co and the HAP carrier improves the catalytic performance of toluene oxidation.

[0020] The present invention does not use a template in the synthesis process, thereby reducing the synthesis cost. After aging, impurities are not removed by washing, but are removed during the calcination of the carrier. The present invention is different from the patent use described in the background technology. The prior art uses HAP as a carrier for sustained drug release after a secondary hydrothermal reaction, while the present invention uses HAP as a carrier to load precious metals for catalytic oxidation of toluene.

[0021] The method for preparing a cobalt-doped catalyst for toluene oxidation reaction provided by the present invention has the advantages of simple preparation method, strong universality, etc., and the prepared catalyst has the advantages of good dispersibility, high activity, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The X-ray powder diffraction spectrum (XRD) of the HAP sample prepared in Example 1-3 of the present invention after calcination; Figure 2 X-ray powder diffraction spectra (XRD) of the HAP samples prepared in Examples 2 and 4 of the present invention after calcination; Figure 3 The nitrogen adsorption-desorption curves (N2 adsorption) of the HAP samples prepared in Examples 1-3 of the present invention are shown; Figure 4 Nitrogen adsorption and desorption curves (N2 adsorption) of HAP samples prepared in Examples 2 and 4 of the present invention; Figure 5 This is an optical photograph of the HAP sample prepared in Example 4 of the present invention; Figure 6 This is a scanning electron microscope image (SEM) of the HAP sample prepared in Example 1 of the present invention; Figure 7This is a scanning electron microscope image (SEM) of the HAP sample prepared in Example 4 of the present invention; Figure 8 Scanning electron microscope image (SEM) of the HAP sample prepared in Comparative Example 1 of the present invention Fig. 9 This is a transmission electron microscope (TEM) image of the catalyst prepared in Example 6 of the present invention; Fig.10 This is a transmission electron microscope (TEM) image of the catalyst prepared in Example 7 of the present invention; Fig.11 This is the toluene oxidation reaction activity diagram of the catalyst described in Examples 1-3 of the present invention; Fig.12 This is the toluene oxidation reaction activity diagram of the catalyst described in Examples 5-8 of the present invention. DETAILED DESCRIPTION

[0023] The following are specific embodiments of the present invention and are combined with the attached Figure 1-12 , the technical solutions of the present invention are further described, but the present invention is not limited to these embodiments; in the following description, specific details such as specific configurations are provided only to help fully understand the embodiments of the present invention. Therefore, it should be clear to those skilled in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present invention.

[0024] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.

[0025] Unless otherwise specified, the materials, practices and experimental equipment involved in the implementation cases of the present invention are all in line with commercially available products in the relevant chemical and biotechnology fields.

[0026] Example 1 The HAP carrier was prepared by the sol-gel method. 1.1805 g of calcium nitrate tetrahydrate (Ca(NO3)2·4H2O) was weighed and dissolved in 34 ml of deionized water. Then 6 ml of phosphoric acid (H3PO4, 0.5 mol / l) was slowly dripped into the calcium nitrate solution and stirred evenly in a 50 ℃ water bath for 0.5 h. NH3·H2O was dripped into the above mixed solution until the pH value remained unchanged. The mixture was allowed to stand for 24 h and freeze-dried. HAP was calcined at 400 ℃ for 2 h to obtain HAP white powder. After being immersed in 1 wt.% chloroplatinic acid solution, the catalyst was placed in a 50°C oven for drying; the dried catalyst sample was then heat treated to obtain Pt / HAP sample Example 1. The XRD spectrum shows that the crystallinity of the sample is low ( Figure 1 ), due to the low calcination temperature of the sample, the specific surface area of ​​the carrier in Example 1 (63.7 m 2 / g) and pore volume (0.6 nm) are the largest, as shown in Table 1.

[0027] Example 2 Weigh 1.1805 g of calcium nitrate tetrahydrate (Ca(NO3)2·4H2O) and dissolve it in 34 mL of deionized water. Then slowly drip 6 ml of phosphoric acid (H3PO4, 0.5 mol / l) into the calcium nitrate solution and stir evenly in a 50 ℃ water bath for 0.5 h. Drop NH3·H2O into the above mixed solution until the pH value remains unchanged, let it stand for 24 h, freeze-dry it, and roast the sample at 600 ℃ for 2 h to obtain HAP white powder; After being immersed in 1 wt.% chloroplatinic acid solution, the catalyst was placed in a 50°C oven for drying. The dried catalyst sample was then heat treated to obtain Pt / HAP sample Example 2.

[0028] Example 3 Weigh 1.1805 g of calcium nitrate tetrahydrate (Ca(NO3)2•4H2O) and dissolve it in 34 ml of deionized water. Then slowly drip 6 ml of phosphoric acid (H3PO4, 0.5 mol / l) into the calcium nitrate solution and stir evenly in a 50 ℃ water bath for 0.5 h. Drop NH3·H2O into the above mixed solution until the pH value remains unchanged, let it stand for 24 h, freeze-dry it, and roast the sample at 800 ℃ for 2 h to obtain HAP white powder; After being immersed in 1 wt.% chloroplatinic acid solution, the catalyst was placed in a 50°C oven for drying; the dried catalyst sample was then heat treated to obtain Pt / HAP sample Example 3. The XRD diffraction peak crystallinity is low ( Figure 1 ), due to the high calcination temperature, the minimum specific surface area value of the catalyst sample is 22.6 m 2 / g (see Table 1).

[0029] Example 4 At room temperature, 2.3654 g of Ca(NO3)2·4H2O and 4.2065 g of citric acid were dissolved in 25 ml of deionized water, placed on a magnetic stirrer, and completely dissolved. Then, 1.3703 g of K2HPO4 was added thereto, and then ammonia water was added to the solution to adjust the pH of the solution to 10.0. Stirring was continued for 0.5 h in a 50 °C water bath, and the mixture was allowed to stand for 24 h, and then freeze-dried. The sample was calcined at 600 °C for 2 h to obtain a HAP white powder, and HAP sample Example 4 was obtained. Optical photographs were taken for this example (see Figure 4 ), it can be observed from the figure that the prepared HAP is lighter than the conventional sample, and the test shows that its bulk density is only 0.436g / ml.

[0030] Example 5 A certain stoichiometric amount of Co(NO3)2 was dissolved in deionized water to prepare a solution of a certain concentration, 60 mg of the HAP carrier described in Example 1 was weighed and placed in a beaker, and the solution was added to the HAP (Co mass fraction was 15%) through a pipette, stirred evenly, and then wrapped with tin foil and placed in a 50°C oven to dry. The dried sample was then heat-treated in a muffle furnace to obtain the catalyst Co / HAP, which is Example 5.

[0031] Example 6 60 mg of the HAP carrier described in Example 1 was weighed and placed in a beaker. Under stirring, the carrier was impregnated with a 15 wt.% cobalt nitrate solution, and then dried and heat-treated at a temperature of 30-90° C. to obtain an impregnated Co-HAP sample. After being impregnated with 1 wt.% chloroplatinic acid solution, the sample was wrapped with tin foil and dried in an oven at 50°C. The dried sample was then heat treated to reduce the precious metal Pt, and the obtained catalyst was labeled as Pt / Co-HAP, i.e., Example 6.

[0032] Example 7 60 mg of the HAP carrier described in Example 1 was weighed and placed in a beaker. It was then impregnated with a 15 wt.% cobalt nitrate solution under stirring, dried at 30-90°C, and then impregnated with 1 wt.% chloroplatinic acid. It was then wrapped in tin foil and dried in an oven at 50°C. The dried sample was then heat treated to simultaneously reduce Pt and Co in a hydrogen atmosphere. The obtained catalyst was labeled Pt-Co / HAP, i.e., Example 7.

[0033] Example 8 The Co-doped HAP carrier was prepared by the sol-gel method. 0.9302 g of calcium nitrate tetrahydrate (Ca(NO3)2·4H2O) and 0.0116 g of cobalt nitrate hexahydrate (Co(NO3)3·6H2O) were weighed and dissolved in 34 ml of deionized water. Then 6 ml of phosphoric acid (H3PO4, 0.5 mol / l) was slowly dripped into the calcium nitrate solution and stirred evenly in a 50 ℃ water bath for 0.5 h. The diluted NH3·H2O was dripped into the above mixed solution until the pH value remained unchanged, and the mixture was allowed to stand for 24 h, freeze-dried, and the sample was heat-treated to obtain the Co-doped HAP carrier. After being immersed in 1 wt.% chloroplatinic acid solution, the catalyst sample was placed in an oven at 50°C for drying, and then heat-treated to obtain a Co-doped Pt / HAP catalyst, namely, Example 8.

[0034] Comparative Example 1 Preparation of flower-like HAP by hydrothermal method: At room temperature, first, 2.9245 g of EDTA and 1.613 g of NaOH were mixed to prepare a certain concentration of EDTA•2Na solution, and then 2.3615 g of Ca(NO3)2, 0.7925 g of (NH4)2HPO4 and 0.1442 g of SDS were dissolved in 60 ml of deionized water, and placed on a magnetic stirrer to mix and dissolve the two solutions. Finally, 2.4240 g of urea was dissolved in 8 ml of deionized water, and the mixture was added and stirred for 20 min. Subsequently, the solution was transferred into a 100 ml stainless steel autoclave with polytetrafluoroethylene lining, and hydrothermally reacted at 180 °C for 12 h, then cooled to room temperature, and the white precipitate product was centrifuged, washed three times with water, washed once with alcohol until neutral, and dried in an oven at 50 °C to obtain a flower-like HAP material with a bulk density of 0.598 g / ml.

[0035] The catalysts of Examples 1, 2, 3, 5, 6, 7, 8 and Comparative Example 1 were used for the catalytic oxidation reaction of toluene. The total flow rate of the feed gas was 130 ml / min, and the composition was: toluene content 610 ppm, O2 content 20%, N2 as the balance gas, 100 mg of catalyst, and the space velocity was 78,000 ml / h·g cat .

[0036] Table 1 shows the specific surface area, average pore size, and pore volume test results of the three samples of Example 1, Example 2, and Example 3. It can be seen from the table that as the calcination temperature increases, the specific surface area of ​​the sample gradually decreases and the pore size gradually increases. Figure 1 As can be seen from Table 1, the increase of calcination temperature makes the crystallinity of HAP higher, the grain size larger, and the specific surface area lower. 2 / g dropped to 22.6 m 2 / g, the pore size increases from 18.8 nm to 37.7 nm.

[0037] Table 2 shows the specific surface area, average pore size, and pore volume of the two samples of Example 2 and Example 4. It can be seen from the table that the addition of citric acid reduces the specific surface area, average pore size, and pore volume after calcination. 2 / g dropped to 46.8m 2 / g, the pore size decreased from 12.6nm to 6.7nm. Figure 6 , Figure 7 From Table 2, it can be concluded that the addition of citric acid makes the size of HAP larger and the sheet thicker. Fig.12It can be seen that the complete conversion temperature of toluene in Examples 6, 7, and 8 is 230-240°C, which is lower than the complete conversion temperature of toluene in Comparative Example 1. This shows that the cobalt-doped mesoporous Pt / HAP, Pt-Co / HAP, and Pt / Co-HAP catalysts used in the present invention have good catalytic oxidation removal effects of toluene at low temperatures. This is related to the interaction between Ag, Co, and the HAP carrier. The results show that the introduction of Co can enhance the activation of oxygen.

[0038]

[0039]

[0040] Those skilled in the art to which the present application belongs may make various modifications or additions to the specific embodiments described or replace them in a similar manner, but they will not deviate from the inventive concept of the present application or exceed the scope defined by the attached claims.

Claims

1. A method for preparing a cobalt-doped mesoporous HAP catalyst, characterized in that: The steps include: 1). Preparation of precursor HAP colloid: The solutions of the calcium source and the phosphorus source are mixed, magnetically stirred, and the pH value of the solution is adjusted; 2). Preparation of ultra-light mesoporous nano-HAP: The precursor was aged and then freeze-dried to obtain ultralight mesoporous nano-HAP; 3) The ultralight mesoporous nano HAP prepared in step 2) is used as a carrier and prepared by an impregnation method. A cobalt-doped supported Pt catalyst, a supported Co catalyst and a supported Pt-Co catalyst are obtained; 4). Heat-treating any one of the supported noble metal catalysts obtained in step 3) to obtain a Pt / HAP catalyst, a Co / HAP catalyst, a Pt / Co-HAP catalyst, or a Pt-Co / HAP catalyst.

2. The method for preparing a cobalt-doped mesoporous HAP catalyst according to claim 1, characterized in that: The step 1) adopts a sol-gel preparation method, specifically: Dissolve the soluble calcium salt in deionized water, slowly drip the phosphorus source into the calcium salt solution, then drip into the citric acid solution, stir for 0.1-5 h at a temperature of 30-90 °C; then add ammonia water to the solution, adjust the pH value to 8-12, continue stirring for 0.5-6 h, and age for 6-72 h to obtain HAP gel.

3. The method for preparing a cobalt-doped mesoporous HAP catalyst according to claim 2, It is characterized in that In the step 2), the HAP gel is freeze-dried for 12-48 hours to obtain an ultralight mesoporous HAP material.

4. The method for preparing a cobalt-doped mesoporous HAP catalyst according to claim 2, characterized in that: The molar ratio of calcium ions in the soluble calcium salt to phosphorus ions in the phosphorus source is 5:

3.

5. The method for preparing a cobalt-doped mesoporous HAP catalyst according to claim 2, characterized in that: The soluble calcium salt is one of calcium nitrate, calcium chloride or calcium hydroxide; the phosphorus source is one of phosphoric acid, diammonium hydrogen phosphate, disodium hydrogen phosphate or dipotassium hydrogen phosphate.

6. The method for preparing a cobalt-doped mesoporous HAP catalyst according to claim 2, It is characterized in that Citric acid is used as a chelating agent, and the molar ratio of citric acid to soluble calcium salt is 2:

1.

7. The method for preparing a cobalt-doped mesoporous HAP catalyst according to claim 1, characterized in that: The specific steps of obtaining the Co / HAP catalyst are as follows: placing the ultralight mesoporous nano-HAP as a carrier in a beaker and immersing it in a 15 wt.% cobalt nitrate solution, and then drying and heat treating it at a temperature of 30-90°C.

8. The method for preparing a cobalt-doped mesoporous HAP catalyst according to claim 1, characterized in that: The specific steps of obtaining the Pt-Co / HAP catalyst are as follows: placing the ultralight mesoporous nano-HAP as a carrier in a beaker, impregnating 1 wt.% chloroplatinic acid and 15 wt.% cobalt nitrate solution in one step, drying at a temperature of 30-90°C, and then heat treating the dried sample.

9. The method for preparing a cobalt-doped mesoporous HAP catalyst according to claim 1, characterized in that: The specific steps of obtaining the Pt / Co-HAP catalyst are as follows: placing the ultralight mesoporous nano-HAP as a carrier in a beaker, impregnating it with a 15 wt.% cobalt nitrate solution under stirring, drying it at a temperature of 30-90°C, heat-treating it, and then impregnating it with a 1 wt.% chloroplatinic acid solution, and drying it in a 50°C oven; and then heat-treating the dried catalyst sample.

10. Use of the cobalt-doped mesoporous HAP catalyst prepared by the preparation method according to any one of claims 1 to 9 in toluene oxidation reaction.

Citation Information

Patent Citations

  • Preparation method of mesoporous hydroxyapatite / titanium dioxide nanotube array composite material

    CN107190300B